Achieving HIV risk reduction through HealthMpowerment.org, a user-driven eHealth intervention for young Black men who have sex with men and transgender women who have sex with men - Muessig, Kathryn E. (Digit Cult Educ, 2014)
Young, Black men who have sex with men and transgender women who have sex with men (YBMSM/TW) are at disproportionate risk for HIV and other sexually transmitted infections (HIV/STI). HealthMpowerment.org (HMP) is a mobile phone optimised online intervention that utilises behaviour change and gaming theories to reduce risky sexual behaviours and build community among HIV-positive and negative YBMSM/TW. The intervention is user-driven, provides social support, and utilises a point reward system. A four-week pilot trial was conducted with a diverse group of 15 YBMSM/TW. During exit interviews, participants described how HMP components led to behaviour changes such as asking partners' sexual history, increased condom use, and HIV/STI testing. The user-driven structure, interactivity, and rewards appeared to facilitate sustained user engagement and the mobile platform provided relevant information in real-time. Participants described the reward elements of exceeding their previous scores and earning points toward prizes as highly motivating. HMP showed promise for being able to deliver a sufficient intervention dose and we found a trend toward higher dose received and more advanced stages of behaviour change. In this pilot trial, HMP was well accepted and demonstrates promise for translating virtual intervention engagement into actual behaviour change to reduce HIV risk behaviours.